The Application of Point of Care Ultrasound to Screen for Pulmonary Hypertension: A Narrative Review - Danny Yu Jia Ke; Melissa Tso; Amer Johri (CINQUILL Medical Publishers Inc., 2024)
Background: Pulmonary Hypertension (PH) is a condition with several cardiopulmonary etiologies that has the potential of progressing to right heart failure without proper intervention. After a history, physical exam, and investigations, cases of suspected PH typically undergo imaging via a (TTE). This is a resource-intensive procedure that is less accessible in remote communities. However, point of care ultrasound (POCUS), a portable ultrasound administered at the bedside, has potential to aid in the diagnostic process of PH. Methods: The MEDLINE, , and CENTRAL databases were searched to screen the intersection of POCUS and PH. Studies involved adult patients, and only English articles were accepted. Reviews, case reports, unfinished research, and conference abstracts were excluded. Our aim was to identify primary studies that correlated POCUS scan results and additional clinical findings related to PH. Results: Nine studies were included after our search. In these studies, POCUS was effective in identifying dilatation of inferior (IVC); internal jugular vein (IJV); and hepatic, portal, and veins in patients with PH. The presence of pericardial effusion, effusion, or b-lines on POCUS are also associated with PH. Conclusions: This review suggests important potential for the use of POCUS in the initial screening of PH. IVC and basic cardiopulmonary POCUS exams are key for PH screening in patients with . Right-heart dilatation can be visualized, and peripheral veins may be scanned based on clinical suspicion. POCUS offers screening as an extension of a physical exam, with direct visualization of cardiac morphology. However, more studies are required to develop a statistically validated POCUS exam for PH diagnosis. More studies should also be conducted at the primary-care level to evaluate the value of screening using POCUS for PH in less-differentiated patients.